Description of the male of Oxyporus bautistae Márquez & Asiain (Coleoptera: Staphylinidae, Oxyporinae) - Navarrete-Heredia, José Luis; Márquez, Juan (Zootaxa, 2015)
The male of Oxyporus bautistae Márquez and Asiain, 2006 is described based on one specimen from San José del Pacífico, southern Oaxaca, Mexico. Oxyporus bautistae shares with O. mexicanus Fauvel, 1865 the bicolored color pattern in legs (black and orange). The male of O. bautistae has six black spots on tergites and the female has only two black spots; but we cannot explain whether the number of black spots represents a sexual character or individual variation.